Foundation ownership and firm growth - Joern Block; Reza Fathollahi (Review of Managerial Science, 2022)
Prior research has analyzed how different ownership types affect firm growth. Yet, so far, we know little about the effect of foundation ownership on firm growth. This is an important research gap as some of the largest firms in Western and Northern Europe are either fully or partly owned by foundations. Our study addresses this gap and analyzes the effects of foundation ownership on sales and employee growth. Based on a matched sample of foundation- and non-foundation-owned firms from the DACH (Germany, Austria, Switzerland) region, our analyses show that foundation-owned firms grow significantly less than non-foundation-owned firms in terms of sales but not with regard to employees. In addition, we find that the negative effect is stronger for the upper than for the middle or lower quantiles of the growth distribution. Our results can be explained through the characteristics of foundations as owners, particularly their long-term orientation and their goal of preserving the assets of the foundation. It seems that foundations as firm owners avoid the risks associated with extreme sales growth and aim for a risk-averse and conservative growth strategy.
Keywords: C12; C51; C52; 650; Foundation ownership; Foundation-owned firms; Corporate governance; Sales growth; Employee growth; Ownership structure